Searches for new phenomena in events with two leptons, jets, and missing transverse momentum in 139 fb$$^{-1}$$ -1 of $$\varvec{\sqrt{s}}=13$$ s=13 TeV $$\varvec{pp}$$ pp collisions with the ATLAS detector. (Tufts University. Tisch Library., 2023)
Springer Open.